Bacteriological quality of milk / Salwa Sobariah Mat Hussin - Mat Hussin, Salwa Sobariah (2013)
Introduction: Food poisoning results when eat food contaminated with bacteria or other pathogens such as parasites or viruses. Preparation of food in advance of needs combined with improper storage and inadequate cooking, cooling and reheating were the mostcommon factors. One of the causes of food poisoning is contamination of raw milk. Bacteria commonly linked to raw milk and poultry is causing food contamination. Raw milk is not pasteurized, homogenized or frozen, nor has it been altered with additives, chemicals, light or homogenization. Amongst the coliform, Escherichia coli are the most commoncontaminant of raw and process milk. Total plate count, coliform and e.coli count and detection of Salmonella were detennined to analyze the safety and quality of raw milk.